PHONETIC STYLISTIC DEVICES ("Conference on Universal Science Research 2023", 2023)
This article deals with the analysis of phonetic stylistic devices and expressive means in the works of poets. Examples from poetry are given in this research work and they are of great importance for learning stylistics